Synthesis of Rice Husk Mesoporous Silica as pH Responsive Release Material - Pidia Aulia; Saprini Hamdiani; Iwan Sumarlan (Chemistry Education Program, the University of Mataram, 2019)
The synthesis of mesoporous silica as a delivery agent for the ethyl para-methoxycinnamate has been carried out. The study aims to determine the process of mesoporous silica synthesis from sodium silicate from the smelting of rice husk ash, determine the adsorption capacity of mesoporous silica in the ethyl para-methoxycinnamate and the pH responsive release of ethyl para-methoxycinnamate with mesoporous silica as a delivery agent in simulated intestinal and gastric fluids. It was found that mesoporous silica can be synthesized from rice husk ash with a 30% tartaric acid template. Characterization of mesoporous silica using FTIR spectroscopy showed the presence of silanol (Si-OH) and siloxane (Si-O-Si) functional groups. Mesoporous silica from rice husk ash is able as adsorbent for the ethyl para-methoxycinnamate with the adsorption capacity of 8.26 mg/g. The release test of gastric simulation fluid (pH 1.2) showed that the ethyl-para-methoxycinnamate was released from silica for a period of 12 hours. In the intestinal simulation fluid (pH 7.4), the release of the ethyl para-methoxycinnamate occurred slowly at the first hour, then gradually increased at 5 hour up to 12 hour.